EVALUASI KINERJA BANK UMUM SYARIAH DENGAN MENGGUNAKAN INDEKS MAQASHID SYARIAH (STUDI PADA BANK SYARIAH MANDIRI DAN BANK MUAMALAT INDONESIA) - FERDY DWI SETYAWAN ; Nur Khusniyah Indrawati, S.E., M.Si., Dr (Manajemen FEB - UB, 2018)
This study aims to evaluate the performance of sharia commercial banks using the maqasid al-shari’ah index. The maqasid al-shari’ah index is a performance appraisal that illustrates the performance of sharia commercial banks not only from the aspect of profit but also from social and environmental aspects. This research uses quantitative descriptive analysis method. The data that used in this research is secondary data obtained from the sharia bank annual report of each sharia commercial bank official website. The data then analyzed by using Simple Additive Weighting method. The maqasid al-shari’ah index measures three performance aspects which consist of educating individual, establishing justice, and public interest. The final result of this study shows that Bank Muamalat Indonesia perform better than Bank Syariah Mandiri. Keywords: Performance evaluation, Sharia Commercial Banks, Maqasid AlShari’ah